An Efficient Method for Connected-Component Labeling in 3D Binary Images - Zhao, Xiao; He, Lifeng; Wang, Yongchao; Chao, Yuyan; Yao, Bin; Hideto, Kasuya; Atsushi, Ohta (2018 International Conference on Robots and Intelligent System (ICRIS), 2018)
According Although 3D images have played very important roles in many fields and attracted many attentions, there are few reports on connected-component labeling algorithms in 3D binary images. An efficient method for connected-component labeling in 3D binary images is presented, and the number of times for combining equivalent labels for processing a foreground voxel is decreased. Example analysis demonstrated that the efficiency of connected-component labeling can be greatly improved by our proposed method.